OCCURRENCE OF GASTROINTESTINAL NEMATODES ASPICULURIS TETRAPTERA (NITZSCH, 1821) SCHULZ, 1927 AND SYPHACIA OBVELATA RUDOLPHI, 1802 ON MUS MUSCULUS LINNAEUS, 1758 FROM RESEARCH VIVARIA IN MEXICO - Grano-Maldonado, Mayra I (2014)
Laboratory mice Mus musculus Linnaeus, 1758 are commonly used as important models in veterinary and biomedical research. Forty laboratory mice were collected in four different vivaria at the National Autonomous University of Mexico and evaluated for parasites. Examination of intestinal organs revealed nematode Aspiculuris tetraptera (Nitzsch, 1821) Schulz, 1927 (n=104) and Syphacia obvelata Rudolphi, 1802 (n=1582). Astatistical study was performed to determine host sex preference of infection. Cestode parasites, Rodentolepis nana (Siebold, 1852) synonymous (Hymenolepis nana and Vampirolepis nana) including a potential cause of human cestodiasis, with an emphasis on those pathogens with zoonotic potential. Evident ectoparasites were not present. A review reporting parasites on rodents employed on vivaria in Mexico was elaborated from a database at the National Helminths Collection of the Institute of Biology of the National Autonomous University of Mexico. This is the first report of the occurrence of these nematodes, A. tetraptera and S. obvelata, on M. musculus used and their known geographical distribution.